Pe Peningkatan Keprofesian Guru melalui Workshop Penulisan Manuskrip di Kecamatan Banyubiru, Kabupaten Semarang - Santoso, B. Wahyudi Joko; Hasyim, M. Yusuf Ahmad; Nugroho, Yoyok; Nugroho, Lutfi Hadi; Khoiriyah, Siti; Yusuf, Ahmad Efendi (Institute for Research and Community Services, 2024)
The publication of scientific articles by teachers and school principals in primary schools is not very encouraging for stakeholders. This has two main implications: the lack of seriousness and motivation among teachers to improve their Continuous Professional Development and the delay in their promotions for several years, even up to a dozen years. Based on current data, there are 180 teachers, including civil servant teachers (ASN) and teachers under the Civil Servant Law (PPPK), as well as 19 school principals who have not been able to apply for promotions. The unpreparedness of teachers and school principals in Semarang Regency is the cause of issues in implementing Teacher Certification activities and reporting them. The Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 16 of 2009, dated November 10, 2009, regarding the Functional Position of Teachers and their Credit Points, stipulates that each civil servant teachers must meet certain requirements to be eligible for promotion, including research and publication. The objective of this service is to enhance the participants' competence in producing manuscripts. The methods used in this service include lectures, demonstrations, question-answer, online learning, practical exercises, and simulation method. The outcomes of this service indicate that the Turnitin scores remain relatively high, averaging between 50-60%. Participants often do not adhere to author guidelines and manuscript templates, and there are still a significant number of spelling and grammatical errors (1047 in total). As a result of this service, 14 participants (73.68%) were able to write manuscripts with a grade of B, 4 participants (21.05%) received a BC grade, and 1 participant (5.26%) received a C grade. In conclusion, the participants in this service are now capable of writing manuscripts, although some revisions are still needed.